2017
DOI: 10.1016/j.bios.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid capture and labeling of cells on single domain antibodies-functionalized flow cell

Abstract: Current techniques to characterize leukocyte subgroups in blood require long sample preparation times and sizable sample volumes. A simplified method for leukocyte characterization using smaller blood volumes would thus be useful in diagnostic settings. Here we describe a flow system comprised of two functionalized graphene oxide (GO) surfaces that allow the capture of distinct leukocyte populations from small volumes blood using camelid single-domain antibodyfragments (VHHs) as capture agents. We used site-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…GO solution (4 mg/mL, Sigma-Aldrich) was used as a stock solution, which was diluted with deionized water to 1 mg/mL before the coating of GO. The procedures of GO coating were same as described previously. , In brief, first, cleaned glass coverslips (sonicated for 30 min in acetone, 95% ethanol, and deionized water washing) were subjected to amine-functionalization with 3% 3-aminopropyltriethoxysilane (Sigma-Aldrich) into toluene for 30 min, followed by washing with 95% alcohol and deionized water and then drying by nitrogen gas. The functionalized glass coverslips were immersed in the GO solution for 1 h and placed on a rocker for gentle shaking to allow uniform GO immobilization on its surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GO solution (4 mg/mL, Sigma-Aldrich) was used as a stock solution, which was diluted with deionized water to 1 mg/mL before the coating of GO. The procedures of GO coating were same as described previously. , In brief, first, cleaned glass coverslips (sonicated for 30 min in acetone, 95% ethanol, and deionized water washing) were subjected to amine-functionalization with 3% 3-aminopropyltriethoxysilane (Sigma-Aldrich) into toluene for 30 min, followed by washing with 95% alcohol and deionized water and then drying by nitrogen gas. The functionalized glass coverslips were immersed in the GO solution for 1 h and placed on a rocker for gentle shaking to allow uniform GO immobilization on its surface.…”
Section: Methodsmentioning
confidence: 99%
“…Carboxyl groups on GO substrates were activated through the 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide/N-hydroxysuccinimide coupling reaction followed by immersing in 0.5 mM maleimide−poly(ethylene glycol)-NH 2 (PG2-AMML-400, Nanocs) in PBS for 6 h for carboxyl groups and primary amines bonding covalently. Subsequently, maleimide functional groups of GO substrates were cross-linked by incubating the osteogenic growth peptide with FITC-labeled cysteine CALKRQGRTLYGFGGK(FITC) in a concentration of 20 μg/mL in PBS containing 5 mM tris(2-carboxyethyl)phosphine hydrochloride for 2 h. 27,28 Statistical Analysis. The data were analyzed via one-way analysis of variance using the GraphPad Prism software and represented as the mean ± standard deviation based on at least three independent experiments and eight representative fluorescent images.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Furthermore, several examples exist showing the labeling of proteins with uorescent dyes utilizing SML. The C-terminal modication with oligoglycine-functionalized dyes was performed 53,[125][126][127] as well as the N-terminal modication with LPETG-functionalized dyes. [128][129][130] Wu et al demonstrated that protein labeling can be also performed in living Caenorhabditis elegans cells.…”
Section: Labeling Of Proteinsmentioning
confidence: 99%
“…In addition, transpeptidase can also be used to create site specific modification on VHH since a short peptide recognition sequence can be easily incorporated into recombinant expression vectors. The Ploegh group incorporated the sortase recognition motif, LPXTG, at the C terminus of VHHs, which can then be used for installation of a short GGG peptide with a biorthogonal handle ( Figure 4 B) [ 55 , 56 , 68 , 69 , 70 ].…”
Section: Current Conjugation Methodsmentioning
confidence: 99%